Methodology for assessing the life cycle processes of scaffolds - Chernobrovchenko, Vadym; Dyadyura, Kostiantyn (Видавництво Львівської політехніки, 2022)
Due to the increase in diseases in the musculoskeletal system, regenerative medicine is now developing various bone substitutes. Not all scaffolds, due to their shortcomings, are applied for every application. Patients should be provided with basic product information and other warnings about health risks or measures to be taken. From the establishment of the purpose of the biomaterial to apply, several stages of the life cycle can pass. To ensure the biocompatibility of medical devices, there is a legislative framework and standards. They cover the full cycle from testing to market authorization, surveillance, and recall (ISO 15225:2010, ISO/IEC 33001:2015). We have developed the life cycle of bone substitutes and can offer an approach to evaluate operations based on the requirements of the ISO/IEC 33001:2015 series.
Keywords: Bone substitute; Life cycle; Risk assessment; Biocompatibility; Process assessment